Nina Stepanenko: CORRESPONDENCE OF HRYHORIY KOCHUR AND MYKOLA LUKASH (1958–1971): LINGUISTIC STORIES - Stepanenko, Nina (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Аbstract. Intoduction. Ukrainian epistolary discourse, the formation of which in chronological and social aspects dates back to the XXIII century, is one of the most pressing linguistic, sociolinguistic, literary, cultural issues. The object of this study is the correspondence of two prominent Ukrainian interpretors of the second half of the twentieth century – Hryhoriy Kochur (46 correspondences) and Mykola Lukash (19 correspondences). Purpose. The aim of the work is to analyze linguistic plots in the studied epistolary corpus, which are related to important issues of theory and practice of literary translation, language situation in the Soviet Union of that period, interlingual contact, interaction of literary language and dialects, archaization and folklorization of translation language, communicative and pragmatic code of the Ukrainian language.